Patient-centered Reporting in Radiology: A Single-site Survey Study of Lung Cancer Screening Results. Issue 6 (24th November 2021) - Barrett, Spencer K.; Patrie, James; Kitts, Andrea B.; Hanley, Michael; Swanson, Christina M.; Vitzthum von Eckstaedt, Hans; Krishnaraj, Arun
Abstract : Purpose: This study aimed to assess whether patients preferred traditional or patient-friendly radiology reports and, secondarily, whether one reporting style led to a subjective improvement in patients' understanding of their imaging results and next steps in their clinical care. Materials and Methods: This randomized study included patients who had previously enrolled in an institutional comprehensive lung cancer screening program. Three hundred patients were randomly selected from the program database to receive both traditional and patient-centered radiology reports. Randomization also occurred at both the risk level of the fictitious test results (low, intermediate, or high) and the order in which the reports were read by each participant. Participants completed a survey providing demographic information and indicating which report style was preferred and which report style led to a better understanding of screening results and future options. In addition, each report style was rated (from 1 to 5) for clarity, understandability, attractiveness, and helpfulness. Results: A total of 46 responses for report preference data and 41 responses for attribute rating data were obtained. Overall, participants demonstrate a preference for patient-friendly reports (65.2%) over traditional reports (21.7%). On a 5-point scale, average ratings for patient-friendly reports were higher than traditional reports by 1.2 ( P <0.001) for clarity, 1.5 ( P <0.001) for understandability, 1.5 ( P <0.001) for attractiveness, and 1.0 ( P <0.001) for helpfulness. Conclusion: Data suggest that patients prefer patient-friendly reports over traditional reports and find them to be clearer, more comprehensible, more attractive, and more helpful.